2019
DOI: 10.1186/s12955-019-1137-6
|View full text |Cite
|
Sign up to set email alerts
|

A head-to-head comparison of EQ-5D-5 L and SF-6D in Chinese patients with low back pain

Abstract: Background The comparative performance of the 3-level EuroQol 5-dimension and Short Form 6-dimension (SF-6D) has been investigated in patients with low back pain (LBP). The aim of this study was to explore the performance including agreement, convergent validity as well as known-groups validity of the 5-level EuroQol 5-dimension (EQ-5D-5 L) and SF-6D in Chinese patients with LBP. Methods Individuals with LBP were recruited from a large tertiary hospital in China. All su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
28
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 59 publications
7
28
2
Order By: Relevance
“…18,20,21 Ye et al and Cheung et al used the EQ-5D-5L, but did not construct predictive models. 14,15 In addition, the variability explained by our model is very high and our results and distribution of utility scores and specific questionnaires are similar than other cohorts with the same problematic, even if it is in other regions. 14,15 Another strength is that no ceiling effect was observed in our cohort for EQ-5D-5L as in the study by Ye et al where the ceiling effect is very small (0.4%) 14 but different from Cheung et al study who have 14% for EQ-5D-5L.…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…18,20,21 Ye et al and Cheung et al used the EQ-5D-5L, but did not construct predictive models. 14,15 In addition, the variability explained by our model is very high and our results and distribution of utility scores and specific questionnaires are similar than other cohorts with the same problematic, even if it is in other regions. 14,15 Another strength is that no ceiling effect was observed in our cohort for EQ-5D-5L as in the study by Ye et al where the ceiling effect is very small (0.4%) 14 but different from Cheung et al study who have 14% for EQ-5D-5L.…”
Section: Discussionsupporting
confidence: 68%
“…This finding is consistent with two studies that found similar correlation between EQ-5D-5L and ODI. 14,15 Ye et al found a higher correlation (r=−0.828) and Cheung et al found exactly the same correlation (r=−0.770). On the other hand, we have a better correlation than other studies that had only moderate correlations around 0.5.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations